FOREIGN TOURIST’S FOOD PREFERENCES IN LOMBOK: A QUALITATIVE RESEARCH IN CUSTOMER BEHAVIOR - Sudiartha Athar, Handry; Josman, Lady Faerrosa; Hermanto (Dinasti International Journal of Digital Business Management, 2020)
Customer behavior is one of the challenging studies in marketing. Most of all, the customer’s behavior towards a tourism destination’s product such as food or as we often call gastronomy. This study is a qualitative research aimed to know what’s behind the food preferences of foreign tourist from different countries (such as Australia, Finland, Japan, Malaysia, and the UK), what motivates them when choosing a certain food during their holiday. In-depth interview along with keen observation were held to get sufficient information and deep results on the purpose of the study. This study was held in Lombok and ten participants were being interviewed. The results indicate that there are three main aspects that affect the participants in choosing their food when in a tourism destination: a) Exposure effect; b) Intention to looking for new experiences and/or based on past experiences; and c) The food aspects. This study surely answers that providing sufficient information to the international market of our tourism industry is a big must as they surely will search for related information before deciding on what to consume in a certain destinations as well as providing them with good quality culinary and a long life experiences that they can cherish in the future.